Space (translation. a transdisciplinary journal, 2022)
To think of the modern city—Cairo, London, Istanbul, Lagos or Buenos Aires—is to experience a perpetual translating machine. Economical, cultural and historical forces are here locally configured and acquire form, substance and sense.These days much attention is given to how global flows become local realities in the multiple realisations of ‘globalisation’, but the archive that the city proposes actually represents an altogether deeper set of sedimentations.